Task Modality Effects on the Production and Elaboration of Language-Related Episodes: A Study on Schoolchildren’s Interactions in a Foreign Language - Francisco Gallardo-del-Puerto; María Martínez-Adrián (Languages, 2022)
Task-modality has been found to constrain the production of LREs in adults and children. However, there are no studies with young learners that have offered a comprehensive analysis of LREs. To this end, this paper will examine the effect of task-modality on the features targeted in them, as well as on their level of engagement/elaboration during primary-school learners’ performance of a task containing both an oral and a written component (OW), and an only oral task with an editing phase (OE). In general terms, both tasks fostered more elaborate meaning-focused LREs than form-focused LREs, while a higher level of engagement with the language was obtained in the OW task. A fine-grained analysis of the different targets indicated that while in terms of meaning-focused LREs, the OW task led the learners to attend to and elaborate discussions on word choice, the OE task enhanced learners’ focus and engagement in word meaning. As for form-focused LREs, the OW task fostered a greater focus on morphosyntactic aspects and spelling, with a higher engagement in the latter. Morphosyntactic aspects were also the target of learners’ discussions in the OE task together with phonological aspects, with slightly more elaborate discussions in the latter.